Optimizing Hepatitis C Therapy in HIV/hepatitis C Virus (HCV) Coinfected Patients: Analysis of HCV Viral Kinetics on Treatment - Paul Damien James; David KH Wong (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Hepatitis C virus (HCV) infection is potentially curable, but the sustained virological response (SVR) has been shown to be lower in patients coinfected HIV. A single-centre experience treating individuals with HCV and HIV coinfection is reported.